Pengaruh Variasi Suhu Dan Durasi Pembakaran Terhadap Kuat Tekan Beton Pasca Bakar - Juhariadi Juhariadi; Andre Novan; Alex Kurniawandy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The significant change of temperature as in the event of fire will have an impact on concrete structures, cracked at the surface of structure, damage / collapse, and discoloration. This research was carried out on samples of concrete cubes K350 with the size of 15 cm x 15 cm x 15 cm. Combustion also was carried out at 600 °C, 800 °C, and 1000 °C temperatures with holding time for 0.5 , 1 , 1.5 , dan 2 hours. The cooling process is done by allowed to stand for 24 hours at room temperature. The test results were obtained at the temperature of at 600 °C, 800 °C, and 1000 °C compressive strength decreased by 6.26%-26.30%, 11.99%-34.53%, and 23.08%-66.37. This research shows that the highest of temperatures gives a greater impact on reduction of concrete compressive strength and the concrete surface, compared with the increase of combustion duration. Through this research regression give equations that can be used to calculate the residual compressive strength of the other combution temperatures. Keywords : fire, compressive strength, porosity, temperature, duration